Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation \( 2^{x-2} + 2^{3-x} = 3 \), follow these steps:
1. Introduce a substitution to simplify the equation:
Let \( y = 2^x \). Therefore, \( 2^{x-2} = \frac{y}{4} \) and \( 2^{3-x} = \frac{8}{y} \).
2. Rewrite the equation with the substitution:
[tex]\[ \frac{y}{4} + \frac{8}{y} = 3 \][/tex]
3. Multiply through by \( y \) to clear the fractions:
[tex]\[ y \cdot \frac{y}{4} + y \cdot \frac{8}{y} = 3y \][/tex]
[tex]\[ \frac{y^2}{4} + 8 = 3y \][/tex]
4. Multiply all terms by 4 to eliminate the denominator:
[tex]\[ y^2 + 32 = 12y \][/tex]
5. Rearrange into standard quadratic form:
[tex]\[ y^2 - 12y + 32 = 0 \][/tex]
6. Solve the quadratic equation:
Use the quadratic formula \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 1 \), \( b = -12 \), and \( c = 32 \).
[tex]\[ y = \frac{12 \pm \sqrt{144 - 128}}{2} \][/tex]
[tex]\[ y = \frac{12 \pm \sqrt{16}}{2} \][/tex]
[tex]\[ y = \frac{12 \pm 4}{2} \][/tex]
This gives us the solutions:
[tex]\[ y = \frac{16}{2} = 8 \quad \text{and} \quad y = \frac{8}{2} = 4 \][/tex]
7. Back-substitute to find \( x \):
Recall that \( y = 2^x \). Now solve for \( x \).
For \( y = 8 \):
[tex]\[ 8 = 2^x \implies 2^x = 2^3 \implies x = 3 \][/tex]
For \( y = 4 \):
[tex]\[ 4 = 2^x \implies 2^x = 2^2 \implies x = 2 \][/tex]
Therefore, the solutions to the equation [tex]\( 2^{x-2} + 2^{3-x} = 3 \)[/tex] are [tex]\( x = 2 \)[/tex] and [tex]\( x = 3 \)[/tex].
1. Introduce a substitution to simplify the equation:
Let \( y = 2^x \). Therefore, \( 2^{x-2} = \frac{y}{4} \) and \( 2^{3-x} = \frac{8}{y} \).
2. Rewrite the equation with the substitution:
[tex]\[ \frac{y}{4} + \frac{8}{y} = 3 \][/tex]
3. Multiply through by \( y \) to clear the fractions:
[tex]\[ y \cdot \frac{y}{4} + y \cdot \frac{8}{y} = 3y \][/tex]
[tex]\[ \frac{y^2}{4} + 8 = 3y \][/tex]
4. Multiply all terms by 4 to eliminate the denominator:
[tex]\[ y^2 + 32 = 12y \][/tex]
5. Rearrange into standard quadratic form:
[tex]\[ y^2 - 12y + 32 = 0 \][/tex]
6. Solve the quadratic equation:
Use the quadratic formula \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 1 \), \( b = -12 \), and \( c = 32 \).
[tex]\[ y = \frac{12 \pm \sqrt{144 - 128}}{2} \][/tex]
[tex]\[ y = \frac{12 \pm \sqrt{16}}{2} \][/tex]
[tex]\[ y = \frac{12 \pm 4}{2} \][/tex]
This gives us the solutions:
[tex]\[ y = \frac{16}{2} = 8 \quad \text{and} \quad y = \frac{8}{2} = 4 \][/tex]
7. Back-substitute to find \( x \):
Recall that \( y = 2^x \). Now solve for \( x \).
For \( y = 8 \):
[tex]\[ 8 = 2^x \implies 2^x = 2^3 \implies x = 3 \][/tex]
For \( y = 4 \):
[tex]\[ 4 = 2^x \implies 2^x = 2^2 \implies x = 2 \][/tex]
Therefore, the solutions to the equation [tex]\( 2^{x-2} + 2^{3-x} = 3 \)[/tex] are [tex]\( x = 2 \)[/tex] and [tex]\( x = 3 \)[/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.